PERLINDUNGAN HUKUM OLEH BADAN PENGAWAS OBAT DAN MAKANAN TERHADAP KONSUMEN ANAK DALAM PENJAMINAN MUTU KESEHATAN MAKANAN - Ni Komang Ayu Febriyanti; Ida Ayu Sadnyini (Media Bina Ilmiah, 2023)
Developments among the community, especially in becoming consumers in the field of consumption, are the main elements of traders in supporting their trading business, but traders are not always vying for profit in selling their products to the public, consumers who are not observant in choosing products to consume are usually children. -children, because children in choosing food only choose sweets and eat a lot without thinking about the condition of the food, therefore it is undeniable that children can experience food poisoning, this is where the role of the government and society is to make efforts to protect to consumers and impose sanctions on traders who deliberately sell unhealthy products.The type of research used in writing this article uses a normative juridical approach that is carried out based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this journal research, then the objectives of the research this is to know and explore related to consumer protection, especially children who are victims of food indicated to be toxic which causes children to get sick as well as efforts made by the government related to consumer protection. The results of this study are legal protection efforts carried out by the POM Agency for child consumers in the event of a loss from guaranteeing food quality health is a preventive and repressive legal protection effort. Preventive legal protection efforts if children become victims, namely prosecution of business actors in the form of non-litigation efforts such as reconciliation, giving health care money, refunding money or similar goods and/or services, coaching, supervision, counseling, and warnings to business actors, while repressive protection efforts in the form of litigation efforts such as revocation of production permits and distribution permits, product destruction and settlement of disputes/disputes through the Dispute Settlement Agency (BPSK), carrying out lawsuits to the District Court (PN) privately as contained in Article 45 of Law Number 8 Year 1999 concerning Consumer Protection and group lawsuits contained in Article 46 of Law Number 8 of 1999 concerning Consumer Protection